PostgreSQL 9 administration cookbook : solve real-world PostgreSQL problems with over 100 simple, yet incredibly effective recipes - Riggs, Simon (Packt Pub., 2010)
Over 80 recipes to help you run an efficient PostgreSQL 9.0 database.